Mobile Termination with Asymmetric Networks - Ralf Dewenter; Justus Haucap (Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2003)
This paper examines mobile termination fees and their regulation when networks are asymmetric in size. It is demonstrated that with consumer ignorance about the exact termination rates (a) a mobile network's termination rate is the higher the smaller the network's size (as measured through its subscriber base) and (b) asymmetric regulation of only the larger operators in a market will, ce-teris paribus, induce the smaller operators to increase their termination rates. The results are supported by empirical evidence using data on mobile termination rates from 48 European mobile operators from 2001 to 2003.
urn:nbn:de:gbv:705-opus-1605
Keywords: L96; L51; L13; 330; mobile termination; telecommunications; consumer ignorance; price regulation; Mobilkommunikation; Vertrag; Telekommunikationsgebühr; Telekommunikationspolitik; Staatliche Preispolitik; Konsumentenverhalten; Theorie; EU-Staaten; Vertragsbeendigung